Other-Attentiveness in Video Consultation Openings: A Conversation Analysis of Video-Mediated Versus Face-to-Face Consultations. Issue 6 (23rd November 2019) - Stommel, Wyke; Goor, Harry van; Stommel, Martijn
Abstract: For patients recovering from surgery, a video consultation is a suitable alternative to conventional consultations. Video consultations have been found to be beneficial, but little is known about their organization, compared to face-to-face consultations. In this article, we explore potential extra interactional work conducted by participants in video-mediated consultations. We focus on the beginning of the consultation. Our data consist of 39 recorded, postoperative, oncological consultations, both face-to-face and through video-mediated communication (VMC), which we analyzed using conversation analysis. Although surgeons commonly launched the beginning with an announcement of the pathology report as the reason for the consultation, we found that in VMC, "how are you?" was regularly inserted after the testing of the technology. The question is a suitable strategy, as it displays overt other-attentiveness, while also being medically relevant. However, subsequently, surgeons may unilaterally close the elicited self-report to then address the pathology report. Thus, the "extra interactional work" of other-attentiveness is again attenuated .